Pengaruh Inflasi dan BI Rate Terhadap Pembiayaan Usaha Mikro Kecil dan Menengah (Studi Kasus Pada Bank Umum Syariah) - JAYANTI, SRI DELASMI; DEKY, DEKY ANWAR (I-Economics, 2016)
This study aimed to analyze the effects of inflation and BI rate on UKMK financing in (BUS) from period 2010-2015. The research sample was taken from six banks. The method of sampling was done by using purposive sampling, which is sampling technique with a certain considerations. The hypothesis testing methods used were multiple linear regression analysis. Partial results of this study indicated that inflation has a significant effect on UKMK financing, while the BI Rate no significant effect on the financing of UKMK. Simultaneously, inflation and BI rate influenced UKMK financing.Kata kunci: Inflasi, Bi Rate, Pembiyaan UMKM